Altered Immune Response and Implantation Failure in Progesterone-Induced Blocking Factor-Deficient Mice - Csabai, Timea; Pallinger, Eva; Kovacs, Arpad F.; Miko, Eva; Bognar, Zoltan; Szekeres-Bartho, Julia (Frontiers in Immunology, 2020)
Earlier data suggest that the progesterone-induced mediator PIBF – is involved in implantation. The present study therefore, aims to investigate the consequences of PIBF deficiency during the peri-implantation period. CD1 female mice were injected i.p., with 2 μg anti-PIBF monoclonal antibody on days 1.5 and 4.5 of pregnancy. The number of implantation sites and resorption rates were recorded on day 10.5. PIBF+ decidual NK cells and B cells were detected with immunohistochemistry or immunofluorescence. Decidual and peripheral NK activity was assessed by flow cytometry. A prime PCR array was used for determining differential expression of genes involved in lymphocyte activation and Th1 or Th2 differentiation, in CD4+ and CD8+ spleen cells from pregnant anti-PIBF treated and control mice. Anti-PIBF treatment in the peri-implantation period resulted in impaired implantation and increased resorption rates in later pregnancy. The number of PIBF+ decidual NK cells decreased, while both decidual and peripheral NK activity increased in anti-PIBF treated mice. B cells were absent from the resorbed deciduas of anti¬- PIBF treated mice. The genes implicated in T cell activation, were significantly down regulated in CD4+, and increased in CD8+ of anti-PIBF treated animals. The gene for IL-4 was significantly down regulated in CD4+ cells while that of IL-12A was upregulated in CD8+ cells, of anti-PIBF-treated animals. These data suggest, that the lack of PIBF results in an impaired T cell activation, together with a Th1 differentiation, and increased NK activity, resulting in implantation failure.